Correlation between serum inflammatory factors and psychosomatic syndrome in patients with chronic obstructive pulmonary disease: an observational study - Zhang, Wenjing; Cui, Yujuan; Sun, Ling; Tu, Chunlin; Yu, Yanfang (Frontiers in Psychiatry, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is increasingly prevalent in respiratory medicine, with rising incidence and mortality rates annually. Beyond respiratory implications, it leads to cardiovascular events, osteoporosis, muscle loss, and psychosomatic syndrome, often overlooked yet pivotal in COPD prognosis. Despite this, the relationship between COPD and psychosomatic syndrome remains unclear. This study aimed to explore the correlation between acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in patients and psychosomatic syndrome, alongside peripheral blood inflammatory factors and symptom burden (e.g., modified Medical Research Council [mMRC] and COPD assessment test [CAT]). Identifying high-risk AECOPD patients with psychosomatic syndrome through these markers could enable early intervention and improve prognosis.MethodsThis observational study recruited 202 AECOPD patients admitted to the Respiratory and Critical Care Medicine Department of Shanghai Jiading Central Hospital from March 1st, 2022 and May 1st, 2024. After obtaining consent, we collected demographic data, blood routine results, albumin, prealbumin, lung function metrics, mMRC, CAT scores, and other parameters. We evaluated psychiatric comorbidities using the revised version of the Diagnostic Criteria for Psychosomatic Research (DCPR-R). Binary logistic regression and ROC curve analyses were employed to assess the correlation between inflammatory factors, symptom burden, and psychosomatic syndrome, as well as their diagnostic and predictive value for psychosomatic syndrome.ResultsAmong 202 AECOPD patients, 144 were in the DCPR (+) group and 58 in the DCPR (-) group. The DCPR (+) group had higher white blood cell counts, neutrophil counts, monocyte counts, interleukin (IL)-6 levels, mMRC scores, and CAT scores than those of the DCPR (-) group, (P < 0.05), Albumin and prealbumin levels were significantly lower in the DCPR (+) group than those in the DCPR (-) group (P < 0.05). There were no significant differences between the two groups in terms of age, sex, marital status, years of education, body mass index, smoking history, drinking history, diabetes, hypertension, PaCO2, PaO2, neutral ratio, lymphocyte count, monocyte ratio, FEV1% pred, and FEV1/FVC% (P > 0.05). Multivariate binary logistic regression analysis identified IL-6, mMRC, and CAT score as independent risk factors for psychosomatic syndrome in AECOPD patients. The odds ratios (OR) and 95% confidence intervals (CI) were: IL-6: OR=1.192 (95% CI: 1.091-1.302), P < 0.001; mMRC: OR=1.922 (95% CI: 1.175-3.144), P = 0.009; CAT: OR=1.149 (95% CI: 1.073-1.231), P < 0.001.ConclusionsPeripheral blood IL-6, mMRC, and CAT were independent risk factors for psychiatric comorbidities in AECOPD patients, with good predictive value for psychosomatic integration. Subjective symptoms including cough, phlegm, sleep disturbances, lack of confidence in going out, and difficulty breathing contribute more to psychiatric comorbidities than the objective indicator of FEV1.